DAMPAK POLA ASUH TOXIC PARENTS TERHADAP KESEHATAN MENTAL REMAJA DI KECEMATAN UJUNG KOTA PAREPARE - Dwi Susanto, Junaedi (Jurusan Bimbingan dan Penyuluhan Islam, 2020)
Parenting patterns should be able to provide positive values to children in their personal and social development stages. The impact of toxic parents parenting style greatly affects children’s mental health in adapting to their environment. In this research, the impact of toxic parents on adolescent mental health uses qualitative methods. The research results found a negative effect on the psychological development of children, in this case teenagers. Such as the inability of teenagers to develop their own potential, the inability of teenagers to increase their self-confidence, the inability of teenagers to process emotions.